Clinical Significance of Trochlear Calcifications in the Orbit - Buch, K.; Nadgir, R.N.; Tannenbaum, A.D.; Ozonoff, A.; Fujita, A.; Sakai, O. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Trochlear calcification is frequently seen on CT scans that include the orbits, but prior studies linking this finding to diabetes mellitus were based on selected populations by using relatively thick sections. We assessed the relationship between trochlear calcification and diabetes mellitus and other chronic medical conditions in an unrestricted population by using thin-section CT. MATERIALS AND METHODS: Noncontrast head CT studies performed consecutively on 1000 patients between January and February 2011 were retrospectively reviewed for the presence of trochlear calcifications. Axial 1.25-mm-thick images acquired by 64-detector row CT were reviewed. Medical records were reviewed for chronic medical conditions, including diabetes mellitus, chronic kidney disease, alcoholism, autoimmune conditions, endocrine disorders, serum calcium and alkaline phosphatase levels, and HIV status. Motion-limited studies and patients with limited clinical data were excluded. Statistical analyses were performed by using the Fisher exact test. RESULTS: Thirty-two patients were excluded from analysis. Of the remaining 968 patients, 128 had trochlear calcification (13%). No significant association was observed between diabetes mellitus and trochlear calcifications in patients of any age (P = .40). There was no significant correlation between trochlear calcifications and chronic kidney disease, alcoholism, endocrine disorders, or HIV infection. Statistically significant associations among trochlear calcification, autoimmune conditions, and elevated alkaline phosphatase levels were observed (P < .0001 and P < .0001, respectively). CONCLUSIONS: On the basis of a large unrestricted population with thin-section CT imaging of the orbit, no significant association was observed between trochlear calcifications and diabetes mellitus. A statistically significant association was observed between trochlear calcification and autoimmune disease and elevated alkaline phosphatase levels. ALPalkaline phosphataseCKDchronic kidney diseaseDMdiabetes mellitusSLEsystemic lupus erythematosus